Pengaruh Pupuk Hayati Fumyco Terhadap Pertumbuhan Anakan Pulai Rawa (Alstonia pneumatophora Backer) di Green House - Rahmawati, Reni; Gaman, Sampang; Sudomo, MFA; Fauzi, Fouad; Darung, Untung (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2025)
The cultivation of Swamp Island in peatlands has been widely carried out by communities in Central Kalimantan Province, but it often fails due to various factors, such as land fires and unfavourable environmental conditions. One way to increase the growth of swamp pulai saplings is the use of Fumyco biofertilizer. This study aims to analyse the growth of swamp island saplings. This research was carried out for 3 months from October to December 2024. The research location is in the Green House, Department of Forestry, Faculty of Agriculture, University of Palangka Raya. The research materials and methods used are in the form of measuring bars, polybags, sprinklers, digital cameras and tally sheets. The materials used are peat soil, swamp saplings and Fumyco biofertilizer. Data analysis includes percentage of survival, plant height (cm) and number of leaves. This study used RAL with 5 (five) Fumyco treatments: Control (P0), (P1) 2 grams, (P2) 4 grams, (P3) 6 grams, (P4) 8 grams and (P5) 10 grams. The results showed that the percentage of swamp island saplings in the 10 gram Fumyco treatment had a value of 88.89%, followed by the 2 gram Fumyco treatment of 77.78%, the treatment of 4 grams, 6 grams and 8 grams of 66.67%, while the control treatment was 66.67%. The results of the analysis of Fumyco biofertilizer application on the height and number of leaves of swamp island plants showed no significant difference. This is suspected because the observation time is only 3 months, but visually in the field the treatment has better growth compared to Control.